2011
DOI: 10.1111/j.1365-2966.2011.18878.x
|View full text |Cite
|
Sign up to set email alerts
|

Luminosity function of galaxies in groups in the Sloan Digital Sky Survey Data Release 7: the dependence on mass, environment and galaxy type

Abstract: We perform an exhaustive analysis of the luminosities of galaxies in groups identified in the Sloan Digital Sky Survey (SDSS) Data Release 7. Our main purpose is to perform a detailed study of the Schechter luminosity function parameters: the characteristic absolute magnitude and the faint‐end slope, as a function of group virial mass in order to quantify their dependence on environment. We analyse the trends of the Schechter parameters as a function of group mass for different photometric bands, galaxy popula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 89 publications
5
63
2
Order By: Relevance
“…This can affect the result, since in some of the four magnitude-gap bins we could be dominated by massive clusters, while in others the dominant systems could be groups. Differences can be found in the literature between the Schechter parameters of clusters and groups (e.g., Zandivarez & Martínez 2011). To test this aspect, we ran a Kolmogorov-Smirnov test, which confirmed that the distributions of σ v (which is a mass proxy, as suggested by Munari et al (2013), and it has been obtained from L X ) for the four subsamples that are not different.…”
Section: Caveats Of the Resultsmentioning
confidence: 88%
“…This can affect the result, since in some of the four magnitude-gap bins we could be dominated by massive clusters, while in others the dominant systems could be groups. Differences can be found in the literature between the Schechter parameters of clusters and groups (e.g., Zandivarez & Martínez 2011). To test this aspect, we ran a Kolmogorov-Smirnov test, which confirmed that the distributions of σ v (which is a mass proxy, as suggested by Munari et al (2013), and it has been obtained from L X ) for the four subsamples that are not different.…”
Section: Caveats Of the Resultsmentioning
confidence: 88%
“…The solid line is the luminosity function for semi-analytical galaxies in groups with virial masses higher than 10 13.5 h −1 M and whose brightest galaxy is an elliptical galaxy. Grey region show the results for galaxies in groups in the SDSS DR7 obtained by Zandivarez & Martínez (2011). Upper and lower arrows represent the faint end slope of the luminosity function obtained by Popesso et al (2005) and Zarattini et al (2015), while middle arrow correspond to the value obtained in this work.…”
Section: Fossil Groupsmentioning
confidence: 99%
“…2. The grey region was built from the best-fitting Schechter parameters of the luminosity function of galaxies in groups identified in the SDSS DR7 by Zandivarez & Martínez (2011) 1 . These fits were obtained only for galaxies brighter than M r − 5 log(h) = −17.…”
Section: Fossil Groupsmentioning
confidence: 99%
“…The catalogue of ZM11 comprises 15,961 groups with more than 4 members, adding up to 103,342 galaxies. We refer the reader to Zandivarez & Martínez (2011) and references therein for further details of group identification.…”
Section: The Samplesmentioning
confidence: 99%
“…Just et al (2015) found evidences of preprocessing of galaxies in the infall region of clusters in the redshift range 0.4 < z < 0.8. These authors found that at z ∼ 0.6, the fraction of red galaxies in the infall region is larger than in the field (see also Moran et al 2007 andPatel et al 2011) In this paper, we study the population of galaxies in the infalling region of massive groups taken from Zandivarez & Martínez (2011). We distinguish between galaxies infalling into groups along filaments and those that are in the infalling region but outside filaments, which we refer to as isotropic infalling galaxies.…”
Section: Introductionmentioning
confidence: 99%